Legal Certainty of Corporate Responsibility That Causes Environmental Damage: A Study of the Implementation of Criminal Law Enforcement - Ramadani, Suci; Sumarno; Lumbanbatu, Bima; Purnomo, Sagita; Habibi, Haris (Journal of Innovative and Creativity, 2026)
This research aims to examine in depth the certainty and legal accountability for environmental damage caused by corporate activities, as well as discuss the challenges and obstacles in enforcing criminal sanctions against corporations. This research method is normative juridical with a descriptive-analytical approach to discuss existing legal problems based on laws and regulations and legal norms that apply in society. The results of this study show that the certainty and legal accountability for environmental damage caused by corporate activities in Indonesia have been regulated in Law Number 32 of 2009 concerning Environmental Protection and Management. Corporations as artificial persons can only carry out legal acts through the intermediary of their representatives, so that criminal sanctions in the form of imprisonment are imposed on the management or directors, while corporations as legal entities can only be subject to sanctions in the form of fines and administrative sanctions. The policy of enforcing sanctions against corporations that destroy the environment is implemented through penal and non-penal approaches. The penal approach is realized through the enforcement of criminal law based on the provisions of the Criminal Code and Law Number 32 of 2009 concerning PPLH. Meanwhile, non-penalties are carried out through the application of the principles of Good Corporate Governance in the company's internal governance, and the implementation of the Corporate Social Responsibility (CSR) program.